Group 1 salts of the imino(phenoxide) scaffold: Synthesis, structural characterization and studies as catalysts towards the bulk ring opening polymerization of lactides. (January 2015) - Ghosh, Swarup; Chakraborty, Debashis; Varghese, Babu
Graphical abstract: Highlights: Complexes of alkali metals containing imino (phenoxide) scaffold described. Potent catalysts for controlled polymerization of lactides. Moderate control in stereochemistry. Polymerization pathway identified. Abstract: A series of lithium, sodium and potassium salts containing various iminophenoxide ligand scaffolds have been successfully synthesized in high yields and purity. These complexes were completely characterized with different spectroscopic techniques and single crystal X-ray diffraction studies on a few of them. These compounds were found to be active towards the solvent free ring opening polymerization (ROP) of L -lactide ( L -LA) and rac -lactide ( rac -LA), yielding polymers with high number average molecular weight ( M n ) and controlled molecular weight distribution (MWDs). Poly(lactic acid) (PLA) derived from the ROP of lactides using the Na complexes showed a close proximity between the observed M n and theoretical molecular weight ( M n theo ). In addition, the MWDs were found to be narrow. These complexes were also found to be active for the ROP of lactides in the presence of benzyl alcohol as a co-initiator. The kinetics and mechanistic studies associated with these polymerizations have been performed and reported.